Jaringan Syaraf Tiruan Untuk Akreditasi Sekolah Menengah Atas/Madrasah Aliyah - DARIYO DARIYO; ROSY DASMITA (JURNAL ILMU PENGETAHUAN & SISTEM INFORMASI (JIPSI), 2018)
ABSTRACT Education Unit Senior High School / Madrasah Aliyah must have a school accreditation ratings, as listed in the Regulation of the Minister of National Education Republic of Indonesia No. 52 of 2008. Obtaining accreditation ratings from the implementation of school education units to eight National Education Standards. The algorithm used the Backpropagation with Momentum. Neural network used has one input layer consisting of 8 nodes, one hidden layer with n nodes are randomly determined by the activation function, and an output layer with 3 nodes form a prediction rank accreditation, accreditation B and accreditation C with the function of accreditation purelin activation. The data is separated into two parts, ie data to be trained and the data that will be tested. Training and testing was conducted using the software Matlab 6.1 with the tested network architecture that is 8-2-1, 8-5-1, 8-9-1, and 8-12-1, which concludes the result of processing with matlab 21 for data sharing training and 21 data for testing with the architectural pattern of 8-5-1 is the best pattern with the percentage of 100% truth. Keywords: Artificial neural network, backpropagation, accreditation, school.